Placing Irish Social Work in a Global Context: Assembling International Comparisons Through the Literature - Flynn, Susan (My University, 2020)
There is an absence of literature that places social work practice in Ireland within a global context. This circumstance is obstructive to students and practitioners of social work in Ireland, who must increasingly demonstrate understanding of social work as an international endeavour. Ireland is also steadily more globalised and multi-cultural. In social work, related changes underway include increased transience of persons across national lines, and complex transnational social problems. In this context, social workers may broaden their understanding of Irish practice through drawing upon learning from elsewhere. To facilitate this, a theoretically informed critical commentary on the literature is presented in this article. The specific focus is on globalisation in the Republic of Ireland. The core argument of the paper is that variance in international socioeconomic wellbeing must be better understood by social work students and practitioners in Ireland, as a response to intensifying globalisation. In developing this argument, two lines of inquiry are pursued. Firstly, focused commentary on the literature on socioeconomic wellbeing and globalisation is presented. This operates around four emergent themes, which are respectively: poverty and economic inequality; life expectancy and health; quality of life and personal safety, and conflict and political strife. Secondly, a composite conceptual framework on the social construction of social work is presented, and applied, to inform discussion and analysis. In conclusion, global cognisance for social workers in Ireland would seem increasingly pertinent and compelled by processes of globalisation.
PUBLISHED
Available free at: https://arrow.tudublin.ie/ijass/vol20/iss1/3
Keywords: Social work; Global; Globalisation; International; Literature